Construction of a Mathematical Model of Multiobjective Optimization on Permutations - Koliechkina, L.M.; Dvirna, O.A.; Nahirna, A.M. (Control systems & computers, 2020)
The article is devoted to the problem of constructing and solving mathematical models of applied problems as multiobjective problems on combinatorial configurations. This question is actual branch because any task of optimal design of complex economic and technical systems, technological devices, planning and management etc. requires that the desired solution be found consider many criteria. It is used transfer to Euclidian combinatorial configurations and using of discrete optimizations methods. Method for solving such problems is considered and it includes the analyzing of structural graph of Euclidean combinatorial configurations sets. These methods can be modified by combining with other multiobjective optimization approaches depending on the initial conditions of the problem. Models for defining real estate contribution plans and production planning as multiobjective discrete problems are proposed. These models can be supplemented as needed by the required functions and, depending on the initial conditions, are presented as tasks on different sets of combinatorial configurations. Мета. Стаття присвячена побудові багатокритеріальних математичних моделей прикладних задач на комбінаторних конфігураціях та їх розв’язанню. Це питання є актуальним, тому що будь-яка задача оптимального проектування складних економічних і технічних систем, технологічних пристроїв, планування і управління вимагає, щоб було знайдено бажаний розв’язок з урахуванням багатьох критеріїв. Методи. В статті здійснюється перехід до евклідових комбінаторних конфігурацій, використовуються методи дискретної та багатокритеріальної оптимізації. Результати. Побудовано модель для визначення планів вкладу в нерухомість і виробничого планування, яка представлена як багатокритеріальна дискретна задача. Представлено метод розв’язання такої задачі, що включає аналіз структурного графа множин евклидових комбінаторних конфігурацій. Даний метод може бути змінений шляхом сполучення з іншими багатокритеріальними методами оптимізації в залежності від початкових умов задачі. Цель. Статья посвящена проблеме построения многокритериальных математических моделей прикладных задач на комбинаторных конфигурациях и их решению. Этот вопрос является актуальным, потому что любая задача оптимального проектирования сложных экономических и технических систем, технологических устройств, планирования и управления требует, чтобы было найдено желаемое решение с учетом многих критериев. Методы. В статье используется переход к евклидовым комбинаторным конфигурациям, а также методы дискретной и многокритериальной оптимизации. Результаты. Построена модель для определения планов вклада в недвижимость и производственного планирования как многокритериальная дискретная задача. Представлен метод решения такой задачи, включающий анализ структурного графа множеств евклидовых комбинаторных конфигураций. Этот метод может быть изменен путем сочетания с другими многокритериальными методами оптимизации в зависимости от начальных условий задачи.